A combined deep inelastic neutron scattering and ab initio lattice dynamics study of the hydride anion dynamics and bonding in La2LiHO3 oxyhydride. (17th October 2019) - Fjellvåg, Øystein S; Krzystyniak, Matthew; Vajeeston, Ponniah; Sjåstad, Anja O; Armstrong, Jeff
Abstract: Kobayashi et al (6279) (Science 2016, 351) reported recently the existence of pure H - conductivity in the oxyhydride La2− x − y Sr x + y LiH1− x + y O3− y, while demonstrating its functionality through a prototype solid-state Ti/La2 LiHO3 /TiH2 battery. In this study, we probe the atomistic motion of La2 LiHO3 obtained by the promising halide salt flux method, via a combination of deep inelastic neutron scattering (DINS) and ab initio lattice dynamics (LD) calculations verified by vibrational inelastic neutron spectroscopy (INS). We successfully describe the measured momentum distributions from DINS via our LD calculations, without observing any diffusion activation over the temperature range reported by Kobayashi et al. This observation is corroborated by model predictions from our LD study, which reveals that the hydride anions remain bound within a 3D-harmonic potential. We conclude that with the current synthesis parameters, the method produces a vacancy free lattice, and that a necessary ingredient for diffusive motion of H - is the presence of a large population of vacancies. Based on the harmonic prediction for the hydrogen kinetic energy, we derive a picture of the evolution of the effective bonding potential for the hydride anions, and link this to the dynamics associated with decomposition of the oxyhydride.